Gender dimorphic M1 excitability during emotional processing: a transcranial magnetic stimulation study - Fanghui Qiu; Yu Zhou; Lanlan Zhang; Jian Zhang; Hui Liu (PeerJ, 2022)
Background It is widely held that emotions prime the body for action. However, the influence of gender on primary motor cortex (M1) excitability during emotional processing is not well explored. Methods Using single-pulse transcranial magnetic stimulation (TMS), we stimulated the right or left M1 at 150 ms and 300 ms after emotional stimulation onset (presentation of negative, neutral, and positive pictures to male and female subjects). Motor-evoked potentials (MEPs) ratio induced by single-pulse TMS was used to assess changes in corticospinal excitability. Results In response to right M1 stimulation, males demonstrated higher MEP ratios following presentation of negative pictures at 150 ms while MEP ratios in response to presentation of positive pictures were greater at 300 ms. Furthermore, male subjects showed larger MEP ratios in right M1 versus left M1 at 300 ms after initiation of positive pictures, indicating lateralization of motor excitability in male subjects. Conclusions The current study thus provides neurophysiological evidence to support gender differences and functional lateralization of motor excitability in response to emotional stimuli.